2000
DOI: 10.1148/radiology.217.3.r00dc21685
|View full text |Cite
|
Sign up to set email alerts
|

US-guided Transthoracic Cutting Biopsy for Peripheral Thoracic Lesions Less than 3 cm in Diameter

Abstract: US-guided transthoracic cutting biopsy appears to be a safe and effective method for diagnosing peripheral thoracic lesions less than 3 cm in diameter. The high diagnostic accuracy for benign lesions and metastatic lung cancer can help prevent surgery in many cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
3
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 32 publications
5
66
3
5
Order By: Relevance
“…In our series, we found three cases in which post-procedual CT showed a thin blood layer around the lesion. Adequacy rate of peripheral pulmonary or pleural lesion biopsy performed with a non fine needle is reported to be between 89.5% and 97% with CT guidance (6,9,10,23) and between 76%and 96 % with US guidance (17,19,20). Our values are comparable with those reported in the literature.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In our series, we found three cases in which post-procedual CT showed a thin blood layer around the lesion. Adequacy rate of peripheral pulmonary or pleural lesion biopsy performed with a non fine needle is reported to be between 89.5% and 97% with CT guidance (6,9,10,23) and between 76%and 96 % with US guidance (17,19,20). Our values are comparable with those reported in the literature.…”
Section: Resultssupporting
confidence: 86%
“…However, US has been described as a useful tool in the characterization of undetermined pleural or sub-pleural pulmonary nodules (13,16) when no aerated lung is interposed in between . Also, US can be used as a safe and effective method with which to guide biopsies of masses abutting the chest wall (5,(17)(18)(19)(20). Major advantages of this imaging modality are that US enables real time multiplanar monitoring of the procedure and can be performed at the patient bedside, without the use of ionizing radiation .…”
Section: Introductionmentioning
confidence: 99%
“…Pneumothorax reportedly occurs in 7e 15% of patients who undergo blind thoracentesis, but the frequency drops to 0.5% when US needle guidance is used [42,43]. In the past 10 years, we have performed 1480 diagnostic or therapeutic thoracenteses under US guidance.…”
Section: Invasive Pleural and Pulmonary Proceduresmentioning
confidence: 99%
“…Anterior mediastinal lesions are clinically approachable under US guidance. US scan permits reliable identification of major vessels that should be avoided during the biopsy, the needle tip can be clearly visualized, and the needle can be advanced precisely within the lesion, allowing real-time imaging guidance and a quicker procedure (5). Previous studies found high diagnostic success rates for US-guided biopsies sized 1.5-10 cm (71% to 100%) (6)(7)(8).…”
mentioning
confidence: 99%